Nanoscale gizmos – the novel fluorescent probes for monitoring protein activity - Manzoor, Ovais (Biochem Eng J, 2018)
Nanobiotechnology has emerged inherently as an interdisciplinary field, with collaborations from researchers belonging to diverse backgrounds like molecular biology, materials science and organic chemistry. Till the current times, researchers have been able to design numerous types of nanoscale fluorescent tool kits for monitoring protein–protein interactions through real time cellular imagery in a fluorescence microscope. It is apparent that supplementing any protein of interest with a fluorescence habit traces its function and regulation within a cell. Our review therefore highlights the application of several fluorescent probes such as molecular organic dyes, quantum dots (QD) and fluorescent proteins (FPs) to determine activity state, expression and localization of proteins in live and fixed cells. The focus is on Fluorescence Resonance Energy Transfer (FRET) based nanosensors that have been developed by researchers to visualize and monitor protein dynamics and quantify metabolites of diverse nature. FRET based toolkits permit the resolution of ambiguities that arise due to the rotation of sensor molecules and flexibility of the probe. Achievements of live cell imaging and efficient spatiotemporal resolution however have been possible only with the advent of fluorescence microscopic technology, equipped with precisely sensitive automated softwares.